2010
DOI: 10.3109/02770901003792833
|View full text |Cite
|
Sign up to set email alerts
|

Eosinophil-Derived Neurotoxin in Childhood Asthma: Correlation With Disease Severity

Abstract: These findings suggest that serum EDN is a useful marker for identifying disease activity in children with asthma. EDN levels may better reflect disease severity than ECP levels or total eosinophil counts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
41
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(57 citation statements)
references
References 31 publications
3
41
1
Order By: Relevance
“…It has been suggested that the secretory activity of eosinophils - a combination of concentration of eosinophils and their propensity to release degranulation products - may be a key marker of disease activity and is more accurately measured by eosinophil degranulation products such as EDN and ECP [135]. Kim et al [136] found significant differences in EDN and ECP levels in asthmatics during both acute and stable phases when compared to controls. Thus, EDN, along with ECP, may aid in the diagnosis of asthma.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been suggested that the secretory activity of eosinophils - a combination of concentration of eosinophils and their propensity to release degranulation products - may be a key marker of disease activity and is more accurately measured by eosinophil degranulation products such as EDN and ECP [135]. Kim et al [136] found significant differences in EDN and ECP levels in asthmatics during both acute and stable phases when compared to controls. Thus, EDN, along with ECP, may aid in the diagnosis of asthma.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, EDN, along with ECP, may aid in the diagnosis of asthma. It has been suggested by several groups that EDN is more useful than ECP in evaluating disease severity [136-138]. This may partially be due to EDN's recoverability, as ECP is a sticky and more highly charged protein [129].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore eosinophil granule protein and EDN released by eosinophils, and eotaxin-3 have been studied as other possible biomarkers of EoE. Blood, urine or tissue levels of eosinophil granule proteins and EDN are elevated in eosinophilic associated diseases 2-6. However, information regarding localization of EDN in the diseased tissues has not been available.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that the secretory activity of eosinophils – a combination of the concentration of eosinophils and their propensity to release degranulation products – may be a key marker of disease activity and is more accurately measured by eosinophil degranulation products such as EDN and ECP [107]. Kim et al [108] found significant differences in EDN and ECP levels in asthmatics during both acute and stable phases when compared with controls. Thus, EDN, along with ECP, may aid in the diagnosis of asthma.…”
Section: The Role Of Eosinophilia In Asthma Development/exacerbationmentioning
confidence: 99%
“…Thus, EDN, along with ECP, may aid in the diagnosis of asthma. It has been suggested by several groups that EDN is more useful than ECP in evaluating disease severity [108,109,110]. This may partially be due to the recoverability of EDN, as ECP is a sticky and more highly charged protein [101].…”
Section: The Role Of Eosinophilia In Asthma Development/exacerbationmentioning
confidence: 99%